Partitioning of the glucoamylase activity at the cell surfaces in cultures of Saccharomyces - Peres, MFS; Souza, C. S.; Thomaz, D.; de Souza, A. R.; Laluce, Cecília [UNESP] (Elsevier B.V., 2006)
Glucoamylases have been used with alpha-amylases for the industrial conversion of starch into glucose. However, little is known about the properties of this glycosylated protein retained in the cell wall of Saccharomyces as well as its role in the saccharification and fermentation of amylaceous substrates, notably in high cell density processes. In most of the strains assayed, decreases in biomass formation were followed by increases in glucoamylase secretion (expressed as U/mg(biomass) in 1 ml of culture) when glucose was exchanged for starch as carbon source or the growth temperature was raised from 30 to 35 degrees C. Despite the losses in viability, significant increases in the activity of the wall fraction occurred when cultures of thermotolerant yeasts propagated at 30 degrees C or washed cells resuspended in buffer solution were heated to 60 degrees C for 60-80 min prior to amylolytic assays. Thus, intact cells of thermotolerant yeasts can be used as colloidal biocatalysts in starch degradation processes. (C) 2005 Published by Elsevier Ltd.
Keywords: yeast; Saccharomyces; glucoamylase secretion; amylolytic enzymes; thermal stability; cell-wall glucoamylase